STUDI TENTANG PENDIDIKAN KRISTEN DALAM GEREJA LOKAL - Ruata, Jayson (Ambassadors: Jurnal Teologi dan Pendidikan Kristiani, 2021)
This paper is a study of Christian education in the local church. The purpose of this study was to gain an understanding of Christian education in the local church. To achieve this goal, the author uses a qualitative research method of literature study, by collecting and analyzing articles, journals, and books that can be used as references. The results of the discussion show that Christian education in the church must see clearly that the congregation is experiencing spiritual growth. Christian education in the church includes nine components, namely: having an education management team, teaching, teaching curriculum, teaching methods, teaching materials or teaching materials, competent teachers or teachers. have students, teaching facilities and infrastructure, teaching evaluation.